(untitled) (Research, Society and Development, 2022)
The objective was to analyze, through an integrative literature review, evidence of research related to motor performance in children and adolescents with autistic spectrum disorder (ASD). The adopted inclusion criteria were: articles published between 1980 and 2020. Searches were performed in Lilacs, Pubmed, Google Scholar, Research Gate and Psycinfo, using the descriptors: autism, “motor skill”, “motor ability” and “motor performance”. It was found 976 records in the initial search, and 61 were selected because they met the established inclusion criteria. Studies carried out with children from first, second and third childhood were found, and a minority carried out with children and adolescents in the same sample. Regarding gender, 73.7% of the studies included in their samples subjects of female and male sexes, 21.3% only involved male subjects and 4.9% only contained female subjects. In most studies, the instruments used to assess the motor performance of children and adolescents with ASD measured motor abilities, while others measured the fundamental motor skills of locomotion and object control, and most studies indicated inferior motor performance of subjects with ASD than peers without the disorder or to children with other disabilities. We highlight that such results suggest motor assessments can be part of the set of tests for the diagnosis of ASD.